National and Religious Discourse in the Novel (Anfal in a Dinner of God and Devils) - Ibrahim, Sarkawt O.; Gharib, Lanja A.; Aahmed, Pakhshan A. (Mitanni Journal of Humanitarian Sciences, 2022)
This research paper, which is entitled “The Patriotic and Religious Discourse in the Novel of “Anfal in a Dinner of God and Demons”, attempts to show the patriotic and religious discourse reflected in the perception of the novel’s author, Hussein Soran. Basically, the novel is a narration of the Anfal campaign (also known as Anfal Genocide) from a different perspective, in which the author shows the patriotic and religious discourse from the perception of Hadjaji Tikriti – a high-ranked officer in Ba’ath’s Regime and an executive character of the Anfal campaign. On the other hand, there exists the contrasting view from the protagonist (i.e., Dildari Melek Xatun) against the patriotic and religious discourse legitimized by the Ba’ath’s regime against the Kurds. Throughout the novel, the author attempts to highlight the concepts of patriotism and religion from the perceptions of two nations, namely, the Arabs as the doers of the Anfal campaign and the Kurds as oppressed and Anfalized.